Children’s perceptions of smokers and nonsmokers - Yazıcı, Hikmet; Ak, İsmail (Journal of Dependence, 2006)
Objective: Initiation of smoking takes place in childhood. One of the factors contributing to this early start is taking adult smokers as their model in their social learning environment. Aim of this study is to determine how children perceive some characteristics of smokers and non-smokers.Method: The participants were 373 volunteer children in this descriptive study. The gender distribution among children was 49.9% girls (n=186) 51.1% boys (n=187). The mean age of the subjects was 12.21 years (SD = 1.56, Maximum = 17, Minimum = 10). Checklist consisting of 29 items was used to assess perceptions of smokers and nonsmokers. In the analysis of the data percentage dispersion and Pearson chi-square analysis were used.Results: Certain significant differences have been found between boys and girls in terms of their perceptions about smokers; 32% of the boys and 42% of the girls perceive the smokers as smart-elegant (x2 = 4.17, df = 2, p
Keywords: Children; social learning; smoking; perception